Measuring the strength of brittle materials by depth-of-penetration testing - Hazell, Paul J. (Maney Publishing, 2010)
Based on an energy conservation model, the strength offered by a number of brittle materials has been calculated from depth-of-penetration (DOP) test results. Each material was completely penetrated by a tungsten carbide cored projectile of known kinetic energy and the residual penetration into a ductile aluminium alloy backing material was measured. The energy transferred to the tile by the projectile has been calculated and has been shown to vary linearly with the tile thickness. From the energy transferred to the armour tile, the mean resisting stress that was offered to the penetrator was calculated and for the materials tested, scaled with the material hardness. This work shows that for DOP testing, where the projectile remains intact, the measured DOP is merely a facet of the ceramic’s hardness and not its true ballistic performance. The possibility of using this method to measure the strength of damaged ceramic is also discussed.
Keywords: depth-of-penetration testing; penetration mechanisms; ceramic armour; modelling; hardness; strength